Implementation of Criminal Sanctions for Violators of International Crimes by the International Criminal Court - Zulkarnain Zulkarnain (Lambung Mangkurat Law Journal, 2024)
In enforcing International Humanitarian Law against violators of crimes that fall under the jurisdiction of the International Criminal Court (ICC) based on the 1998 Rome Statute and previous international crimes that were tried based on the Ad Hoc Court. Norms regarding enforcement mechanisms for International Humanitarian Law can be found in the Geneva Conventions of 1949 and two Additional Protocols I and II of 1977. Apart from that, they can also be found in provisions relating to ad hoc and permanent War Crimes Tribunals, such as the International Criminal Court (ICC). This International Court is a legal instrument that causes violations of international crimes to be said to be effective. To prove that in enforcing International Humanitarian Law, the International Court has tried and punished perpetrators of international crimes, for example, Herman Wihem Georing case through the Nurenburg court with sentenced to death, Matsue Iwane case that Tokyo Tribunal finished, Anto Furundzija case by Yugoslavia court (ICTY), Jean- Paul Akayesu by Ruwanda Tribunal (ICTR), Somalia and Sudan case in processing by ICC. Case of Israel committing war crimes in Gaza during the 2008-2009 period.